The effect of 5A model on behavior change of physical activity in overweight pregnant women - Narmin Ghaderpanah; Hamideh Mohaddesi; Davood Vahabzadeh; Hamidreza Khalkhali (Mashhad University of Medical Sciences, 2017)
Introduction:  Overweight and obesity are considerable challenge for pregnancy care. About 50% of women enter pregnancy with BMI above than 25kg/m2 that can be associated with increased risk in pregnancy. This study was performed with aim to determine the effect of 5A model on behavior change of physical activity in overweight pregnant women. Methods: This randomized clinical trial was conducted on 120 overweight pregnant women referred to health centers of Urmia during 2015-2016. The control group received routine prenatal care, and intervention group received a face to face training program regarding physical activity based on self-management 5A model. This study was performed during 3 months in 5 steps of question, assessment, guidance, agreement, help, and follow-up. Data were analyzed by SPSS software (version 21) and independent t, Chi-square, and covariance analysis tests. P<0.05 was considered significant. Results: The mean of total physical activity level in the control group at the start and the end of the intervention was 74.30 ± 38.89 and 60.37 ± 25.67 MET / min, respectively and in the intervention group was 88.32 ± 15.70 and 35.3 ± 117.30 ±35.14 MET / min, respectively. At the end of intervention, the difference of two groups in terms of physical activity and weight gain was significant. The mean of physical activity at the end of intervention was significantly different after the intervention (P <0.001). Analysis of covariance showed a significant difference between the two groups in physical activity and weight changes after adjusting the confounding variables (P <0.001).  Conclusion: The self-management intervention based on 5A model has an effective role in the changing of pregnant women's behavior and can lead to create motivation, attitude and behavioral modifications. Also it can help them to improve their weight gain according to guidelines through of managing their behavior and life style.